2006
DOI: 10.1111/j.1526-4610.2006.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Topiramate Versus Lamotrigine in Migraine Prophylaxis (The Lotolamp Study)

Abstract: Low-dose topiramate is efficacious in migraine prophylaxis as compared to both placebo and lamotrigine. Lamotrigine in low doses might be beneficial for headache frequency; however, longer trials are required to establish its efficacy on the intensity and frequency of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 26 publications
0
71
0
Order By: Relevance
“…A second, new Class I study comparing lamotrigine 50 mg/day with placebo or topiramate 50 mg/day reported lamotrigine was not more effective than placebo (for both primary endpoints) and was less effective than topiramate in reducing migraine frequency and intensity. 14 The primary outcome measure (responder rate: Ն50% monthly migraine frequency reduction) was 46% for lamotrigine vs 34% for placebo ( p ϭ 0.093, CI 0.02-0.26) and 63% for topiramate vs 46% for lamotrigine ( p ϭ 0.019, CI 0.03-0.31). Treatment-related AEs (rash, giddiness, sleepiness, and gastrointestinal intolerance) occurred in 10% of patients on lamotrigine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A second, new Class I study comparing lamotrigine 50 mg/day with placebo or topiramate 50 mg/day reported lamotrigine was not more effective than placebo (for both primary endpoints) and was less effective than topiramate in reducing migraine frequency and intensity. 14 The primary outcome measure (responder rate: Ն50% monthly migraine frequency reduction) was 46% for lamotrigine vs 34% for placebo ( p ϭ 0.093, CI 0.02-0.26) and 63% for topiramate vs 46% for lamotrigine ( p ϭ 0.019, CI 0.03-0.31). Treatment-related AEs (rash, giddiness, sleepiness, and gastrointestinal intolerance) occurred in 10% of patients on lamotrigine.…”
mentioning
confidence: 99%
“…18 In a second placebo-controlled Class I double-crossover study (reviewed above), topiramate was more effective than placebo and lamotrigine for primary efficacy measures. 14 In the topiramate groups, 15% of patients experienced AEs, most commonly paresthesias, sleepiness, and gastrointestinal intolerance. The placebo group reported gastrointestinal intolerance (3%) and anorexia (3%).…”
mentioning
confidence: 99%
“…Oxcarbazepine was not effective for migraine prophylaxis in a placebo-controlled trial. 28 Lamotrigine was less efficacious for migraine than topiramate in a small double-blind placebo-controlled trial and only marginally better than placebo, 29 confirming the general clinical impression that lamotrigine has low efficacy for migraine.…”
Section: Unique Patient and Antiepileptic Drug Characteristicsmentioning
confidence: 69%
“…Lamotrigine is up to now the only preventive drug which has been shown effective for migraine auras (D'Andrea et al 1999;Lampl et al 2005) but not for migraine without aura (Steiner et al 1997;Gupta et al 2007).…”
Section: Drug Treatmentsmentioning
confidence: 99%